2017
DOI: 10.1002/jemt.22819
|View full text |Cite
|
Sign up to set email alerts
|

Energy dispersive spectroscopy‐scanning transmission electron microscope observations of free radical production in human polymorphonuclear leukocytes phagocytosing non‐opsonized Tannerella forsythia

Abstract: We investigated the association between human polymorphonuclear leukocytes (PMNs) and non-opsonized Tannerella forsythia ATCC 43037 displaying a serum-resistant surface layer (S-layer). When PMNs were mixed with T. forsythia in suspension, the cells phagocytosed T. forsythia cells. Nitro blue tetrazolium (NBT) reduction, indicative of O2- production, was observed by light microscopy; cerium (Ce) perhydroxide deposition, indicative of H O production, was observed by electron microscopy. We examined the relation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…However, the genome of this pathogen encodes an oxidative stress response sensor protein (OxyR) homolog, that acts as a positive regulator for antioxidant gene expression. This can contribute to the resistance of the bacterial community to oxidative stress in the aerobic oral cavity and protect against oxidative burst in leukocytes, which is essential in the dental plaque biofilm formation ( Honma et al, 2009 ; Moriguchi et al, 2017 ).…”
Section: Pathogen-specific Effects On Neutrophil Functionsmentioning
confidence: 99%
“…However, the genome of this pathogen encodes an oxidative stress response sensor protein (OxyR) homolog, that acts as a positive regulator for antioxidant gene expression. This can contribute to the resistance of the bacterial community to oxidative stress in the aerobic oral cavity and protect against oxidative burst in leukocytes, which is essential in the dental plaque biofilm formation ( Honma et al, 2009 ; Moriguchi et al, 2017 ).…”
Section: Pathogen-specific Effects On Neutrophil Functionsmentioning
confidence: 99%
“…Like other effector functions, normal ROS generation by neutrophils is compromised in the context of periodontitis (Figure 1.4). When tested against individual periodontal bacteria in vitro, neutrophils can mount a ROS response of varying degrees against T. denticola , T. forsythia , F. nucleatum , A. actinomycetemcomitans , and P. gingivalis , although the extent of ROS production heavily depends on the strain used, multiplicity of infection, and type of opsonization (Hirschfeld et al., 2017; Katsuragi et al., 2003; Kurgan et al., 2017; Moriguchi et al., 2017; Shin et al., 2008; Yamazaki et al., 2006). Once generated, ROS do not discriminate between host and pathogen cells, and contribute heavily to disease progression.…”
Section: Neutrophil Effector Functions: Before and During The Dysbiotmentioning
confidence: 99%
“…Despite its importance, the specific interaction between T. forsythia and PMNs remains poorly investigated. A study demonstrated that PMNs can phagocytose non-opsonized T. forsythia , leading to ROS production ( 65 ). Additionally, T. forsythia has been shown to adhere to and invade dental follicle mesenchymal stem cells, resulting in diminished PMN chemotaxis, phagocytic activity, and NET formation induced by these cells ( 66 ).…”
Section: Cell-specific Responses To Tannerella Forsythiamentioning
confidence: 99%